2008
DOI: 10.1021/bi801876q
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Link in Petrobactin Biosynthesis: asbF Encodes a (−)-3-Dehydroshikimate Dehydratase

Abstract: The siderophore petrobactin harbors unique 3,4-dihydroxybenzoyl iron-liganding groups. These moieties are known to be synthesized from shikimate pathway precursors, but no reports of the biosynthetic enzymes responsible for this conversion have been published. The gene encoding AsbF from Bacillus thuringiensis 97-27 was overexpressed in an Escherichia coli host. AsbF rapidly and efficiently transforms (-)-3-dehydroshikimate (DHS) into 3,4-dihydroxybenzoate (k(cat)(DHS) = 217 +/- 10 min(-1); K(m)(DHS) = 125 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 21 publications
2
76
0
Order By: Relevance
“…In the first heterologous reaction, 3-DHS is dehydrated to PCA. Several 3-DHS dehydratases (AroZ) acting in various cellular pathways have been identified in different microbial systems (14,15,18,22,28,30,38,39,40). To identify a suitable candidate for the new biosynthetic route in yeast, we chose three different genes, aroZ of the aromatic degradation pathway from Acinetobacter sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first heterologous reaction, 3-DHS is dehydrated to PCA. Several 3-DHS dehydratases (AroZ) acting in various cellular pathways have been identified in different microbial systems (14,15,18,22,28,30,38,39,40). To identify a suitable candidate for the new biosynthetic route in yeast, we chose three different genes, aroZ of the aromatic degradation pathway from Acinetobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…To identify a suitable candidate for the new biosynthetic route in yeast, we chose three different genes, aroZ of the aromatic degradation pathway from Acinetobacter sp. (As-aroZ), aroZ of Podospora anserina (Pa-aroZ) (40), and asbF of the petrobactin biosynthesis pathway from Bacillus thuringiensis (Bt-aroZ) (15,39). The corresponding protein sequences exhibit a very low overall homology of about 17% (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Based on examination of isotopic enrichment in the catecholate moiety of isolated petrobactin, the early steps of the shikimate pathway were identified as the primary source for 3,4-DHB production (Koppisch et al, 2008a). Shortly thereafter, we and Sherman and co-workers independently characterized AsbF as a dehydroshikimate dehydratase (DHSase) (Fox et al, 2008;Pfleger et al, 2008) for direct conversion of 3-dehydroshikimic acid (DHS) to 3,4-DHB. The action of the NRPS-like enzymes AsbCD is ultimately responsible for the activation of 3,4-DHB for transfer onto the citrylspermidine framework to complete the assembly into petrobactin.…”
Section: Bacillibactin Production Uptake and Exportmentioning
confidence: 99%
“…Most other catecholate siderophores contain 2,3-dihydroxybenzoic subunits, which are effectively neutralized by this protein during the host response to infection (27)(28)(29). Previous work has shown that asbF, the final gene of the petrobactin biosynthetic operon, encodes a dehydratase responsible for conversion of 3-dehydroshikimate to 3,4-DHBA (10,14) (Fig. 1C).…”
mentioning
confidence: 99%
“…Conversely, a second siderophore, petrobactin (Fig. 1A), is essential for virulence within current infection models (6,10) and has since become a focus of multiple microbiological, genetic, and biochemical studies (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)20). This mixed catechol-carboxylate siderophore was first isolated from the Gram-negative marine microbe Marinobacter hydrocarbonoclasticus (21).…”
mentioning
confidence: 99%